2014
DOI: 10.1155/2014/271970
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Analysis of FTIR Spectra and GCMS Chromatograms for Evaluation of the Thermally Degraded Vegetable Oils

Abstract: Fourier Transform Infrared (FTIR) and Gas Chromatography Mass Spectrometry (GCMS) are two common instruments used for analysis of edible oils. The output signal is often analysed on the software attached to the workstations. The processing software is usually individualised for a specific source. The output of GCMS cannot be analysed on the FTIR hence analysts often need to juggle between instruments when multiple techniques are employed. This could become exhaustive when a large dataset is involved. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[36,40,44] The band at 964 cm −1 appeared in FPO which had a less intense absorbance was probably due to small amounts of trans isomers formed upon RBD procedure during the production of fresh oil. [46] Several previous studies reported that the band near 967 cm −1 was shifted to higher wavelength and the band near 969 cm −1 was formed as the advanced oxidation process due to the formation of secondary oxidation products such as aldehydes or ketones with the isolated trans double bond. [42,44] Consistent with the previous studies, it was observed that this similar band was shifted from 964 cm −1 (in FPO) to the higher wavelength of 968 cm −1 (in RCO).…”
Section: Aberrations In Ftir Bands Due To the Reduction Of Cis Doublementioning
confidence: 98%
“…[36,40,44] The band at 964 cm −1 appeared in FPO which had a less intense absorbance was probably due to small amounts of trans isomers formed upon RBD procedure during the production of fresh oil. [46] Several previous studies reported that the band near 967 cm −1 was shifted to higher wavelength and the band near 969 cm −1 was formed as the advanced oxidation process due to the formation of secondary oxidation products such as aldehydes or ketones with the isolated trans double bond. [42,44] Consistent with the previous studies, it was observed that this similar band was shifted from 964 cm −1 (in FPO) to the higher wavelength of 968 cm −1 (in RCO).…”
Section: Aberrations In Ftir Bands Due To the Reduction Of Cis Doublementioning
confidence: 98%
“…Spectra were acquired by infrared reflection absorption spectroscopy at a resolution of 4 cm −1 in the range of 4000 to 400 cm −1 . Each spectrum was rationed against a fresh background spectrum recorded from the bare ATR crystal . Prior to collection of each background spectrum, the ATR crystal was cleaned with absolute ethanol to remove any residual.…”
Section: Methodsmentioning
confidence: 99%
“…The carrier gas is pressurized helium 10.5 psi and a total rate of 140 ml/min and a split ratio of 1:50. 10,13…”
Section: Characterization Of Compoundmentioning
confidence: 99%